Checkbox “Other”: An Exploration of the Intersectional Experiences of Nonbinary and Gender-Diverse People of Color (Global Journal of Human-Social Science, 2024)
Nonbinary individuals have been shown to be demographically and experientially distinct from binary transgender individuals Still there continues to be a pronounced lack of focus on nonbinary identities within transgender research Additionally out of the extant research on nonbinary identities few studies explicitly target the intersectional experiences of nonbinary people of color To address this gap this study examined the experiences and perceptions of nonbinary and gender-diverse people of color people whose gender identity does not exclusively align with man or woman and whose racial ethnic identity is not exclusively White at the intersection of LGBTQ and racially ethnically minoritized identity The study utilized two main research questions RQ 1 What are the expectations and preconceptions surrounding nonbinary identities and what are their impacts on both conforming and nonconforming individuals and 2 What kind of influence does culture have on gender development for nonbinarypeople of color Interviews with 12 participants highlighted three RQ1 themes i what it means to look nonbinary ii external perceptions of identity confusion and iii the impact of stereotypes and two RQ2 themes i lack of overlap in LGBTQ and POC spaces and ii identity advantages These results as well as broader research and societal implications are discussed
Keywords: nonbinary; person of color; intersectionality; stereotypes; lived experiences